THE EFFECT OF THE USE OF INTERACTIVE MULTIMEDIA ON THE IMPROVEMENT OF GEOGRAPHY LEARNING ACHIEVEMENT - M. Kurniawan Arif Syaefulloh; Dyah Respati Suryo Sumunar (Geosfera Indonesia, 2018)
Abstract This research aimed to discover the effect of using interactive multimedia on the improvement of (2) geography learning achievement, and (2) learning interest of Grade students IPS of MA El Bayan Majenang. This study was a quasi-experiment using the quantitative approach. The population was 106 grade XI students IPS. A sample of 36 students was established the cluster sampling technique. The data collection used an achievement test, questionnaire on interest in learning, observation and documentation. The data analysis technique used was the inferential statistical technique. The hypothesis testing was performed using the MANOVA test with SPSS 20 program. The results of the study were follows. (1) the error rate (p) geography learning result was 0.009. Because it was smaller than 0.05, there was an effect of the use of interactive multimedia on the achievement of geography learning.(2) the level of error (p) interest in learning was 0.00. Because it was smaller than 0.05, there was an effect of the use of interactive multimedia on the improvement of students' learning interest (3) From MANOVA statistic test, it could concluded that there was an improvement in geography learning achievement and interest of the students before and after the treatment as the experimental class with the average increase of 35.55 and 11.55 respectively. While the improvement of geography learning achievement and interest in learning of the control class was averagely 29.02 and 2.86 respectively. Keywords : Interactive multimedia, Geography Learning Achievement, interest in learning Copyright (c) 2018 Geosfera Indonesia Journal and Department of Geography Education, University of Jember Copyright Notice This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License